POLITIK HUKUM ISLAM DALAM UNDANG-UNDANG JAMINAN PRODUK HALAL : (Analisis Terhadap Program Sertifikasi Halal Gratis 2022 di Sumatera Utara) - Evriza Noverda Nasution (Universitas Mathla’ul Anwar Banten, 2023)
This research was written regarding the politics of Islamic law in the law on halal product namely which is in accordance with the definition put forward by Mahfud MD in his book on legal politics in Indonesia, namely